DETERMINAN PEMBERIAN ASI EKSKLUSIF OLEH IBU YANG MEMILIKI BADUTA - Arif Rahman; Devaki Areta Putrie (Seminar Nasional Official Statistics, 2020)
In determining the degree of health, there are several indicators that can be used, one of which is the Infant Mortality Rate (IMR). In 2017, IMR in Indonesia there are still around 24 cases out of 1000 live births. In fact, the Sustainable Development Goals (SDGs) are targeting that by 2030 the IMR in all countries in the world will drop to 12 cases out of 1000 live births. One of the efforts to reduce IMR is by giving exclusive breastfeeding. During the 2015-2017 period, the percentage of babies who were exclusively breastfed in West Kalimantan was always below the national figure and was even the lowest in Kalimantan. This study aims to describe the characteristics of mothers who have underwent exclusive breastfeeding, determine the influencing variables and analyze their tendency towards exclusive breastfeeding by mothers who have baduta in West Kalimantan Province in 2019. The results of this study are in general, breastfeeding. In West Kalimantan Province, there are many mothers aged 25-34 years, have high school education, live in rural areas, are not working, are not in poor households, and assistants during childbirth are medical personnel. Furthermore, the variables that have a significant effect on exclusive breastfeeding by mothers who have baduta in West Kalimantan Province in 2019 are education level, work status, and household poverty status.